University Education Politicization in Nigeria: Implications and Ways Forward - Ogunode, Niyi Jacob; Atobauka, Ishaya Samaila; Ayoko, Victor Olugbenga (International Journal on Integrated Education, 2023)
Nigerian public universities in recent times have been engulfed with different challenges. Some of the challenges are the indigenization of principal officers/ and the politicization of university education, this paper is aimed to examine the implications of university education politicization in Nigeria. Secondary data and primary data were adopted for the paper. The data were collected from both print and online publications that are related to the title of the paper. The paper concluded that the implication of university education politicization has contributed to the falling standard of university education, poor management, poor international rating, under-development, corruptions and strike actions. The paper recommended that the federal and state government in Nigeria should grant full autonomy to public universities. This will help to prevent political influence in the administration and management of public universities in Nigeria.